Financial Education Development and Planning For Children's Education Funds in Bengkong Permai Batam - Dian Efriyenty; Hikmah; Kahdijah (EQUATOR SINAR AKADEMIA, 2022)
Based on the results of a survey in the field, Bengkong Permai housing mothers experienced financial difficulties, so that many errors occurred in paying debts for their children's education needs in the future. Difficulties in financial management so that mistakes are often made in recording personal finances for Bengkong Permai Housing women, the lack of community skills regarding the products and quality of services provided by the bank, lack of capital in the business can result in stress and reduce trust. The method used is socialization and training. Residents of the Bengkong Permai housing estate have learned the importance of planning early on for their child's education. The more expensive the cost of education from kindergarten, elementary school to undergraduate level, which makes parents have to save their finances. It is hoped that these women will be able to manage their personal finances and increase their income.